Effects of 12-week resistance training during radiotherapy in breast cancer patients - Wiskemann, Joachim; Schmidt, Martina; Klassen, Oliver; Debus, Jürgen; Ulrich, Cornelia; Potthoff, Karin; Steindorf, Karen (Scandinavian journal of medicine & science in sports, 2017)
Exercise is considered to be an effective supportive treatment approach in breast cancer (BC) patients. We conducted a randomized controlled trial to assess the efficacy of a 12-week PRT during radiotherapy. Strength performance was assessed by maximal isokinetic peak torque (MIPT) in two different angular velocities (60°/s and 180°/s) and maximal voluntary isometric contraction for shoulder external and internal rotation, as well as for knee extension and flexion were assessed pre- and post-intervention in 146 patients randomized to PRT or a control group. Statistical analyses were based on analysis of covariance models for the individual changes from baseline to week 13. Intention-to-treat analyses showed significant between-group differences favoring the exercise group (EX) for MIPT in knee flexion and shoulder internal and external rotation (P < 0.05). Subgroup analyses showed borderline significant differences with regard to pretreatment history, revealing that pretreated chemotherapy patients tend to benefit more from PRT than patients without chemotherapy (P = 0.06). Strength gain at the operated arm was significantly higher than at the non-operated arm in EX. PRT was efficacious in increasing upper and lower limb strength in BC patients undergoing adjuvant radiotherapy. Patients with restrictions due to breast cancer-related surgery and pretreated with chemotherapy might benefit the most.